Summary of the Africa Fertilizer and Soil Health Action Plan (2024-2034) - African Union Development Agency- NEPAD; African Union (2024)
This brief provides a summary of the Africa Fertilizer and Soil Health (AFSH) Action Plan. It gives context to Africa’s soil health and fertilizer challenge and provides the AFSH Action Plan results chain and the goals expected to be achieved in the first ten years of implementation (2024-2034). The brief details the four outcome areas and associated outputs and actions. Next it explains the implementation of the AFSH Action Plan describing the leadership structure and its coordination mechanism; the importance of stakeholder engagement and partnership development; and the plan for monitoring, evaluation, accountability and learning. It highlights the Comprehensive Africa Agriculture Development Programme (CAADP) indicators relevant to soil health and the planned phased implementation of the AFSH Action Plan.